Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Certainly! Let's solve the given system of linear equations using matrix methods. The system of equations is:
[tex]\[ \left\{\begin{array}{l} -x - 7y - z = -19 \\ 4x + 4y + 4z = 4 \\ 2x + y + 6z = 7 \end{array}\right. \][/tex]
### Step-by-Step Solution:
1. Write the system in matrix form:
The system of equations can be represented in the form [tex]\(AX = B\)[/tex], where [tex]\(A\)[/tex] is the coefficient matrix, [tex]\(X\)[/tex] is the column vector of variables, and [tex]\(B\)[/tex] is the column vector of constants.
[tex]\[ A = \begin{pmatrix} -1 & -7 & -1 \\ 4 & 4 & 4 \\ 2 & 1 & 6 \end{pmatrix} , \quad X = \begin{pmatrix} x \\ y \\ z \end{pmatrix} , \quad B = \begin{pmatrix} -19 \\ 4 \\ 7 \end{pmatrix} \][/tex]
2. Find the inverse of the coefficient matrix [tex]\(A\)[/tex] (if it exists):
For our purposes, it's sufficient to know that the matrix [tex]\(A\)[/tex] is invertible, and we will use the inverse to find [tex]\(X\)[/tex].
3. Multiply both sides of the equation [tex]\(AX = B\)[/tex] by the inverse of [tex]\(A\)[/tex]:
[tex]\[ A^{-1}AX = A^{-1}B \][/tex]
Since [tex]\(A^{-1}A\)[/tex] is the identity matrix [tex]\(I\)[/tex], this simplifies to:
[tex]\[ IX = A^{-1}B \quad \text{or simply} \quad X = A^{-1}B \][/tex]
4. Calculate [tex]\(X\)[/tex]:
Using the result obtained from computation:
[tex]\[ X = \begin{pmatrix} x \\ y \\ z \end{pmatrix} = \begin{pmatrix} -4 \\ 3 \\ 2 \end{pmatrix} \][/tex]
### Verification:
To ensure the solution is correct, it's good practice to substitute [tex]\(x = -4\)[/tex], [tex]\(y = 3\)[/tex], and [tex]\(z = 2\)[/tex] back into the original equations:
1. For [tex]\( -x - 7y - z = -19 \)[/tex]:
[tex]\[ -(-4) - 7(3) - 1(2) = 4 - 21 - 2 = -19 \][/tex]
2. For [tex]\( 4x + 4y + 4z = 4 \)[/tex]:
[tex]\[ 4(-4) + 4(3) + 4(2) = -16 + 12 + 8 = 4 \][/tex]
3. For [tex]\( 2x + y + 6z = 7 \)[/tex]:
[tex]\[ 2(-4) + 3 + 6(2) = -8 + 3 + 12 = 7 \][/tex]
The solution satisfies all the original equations, confirming that our solution is correct.
Thus, the solution to the system is:
[tex]\[ x = -4, \quad y = 3, \quad z = 2 \][/tex]
[tex]\[ \left\{\begin{array}{l} -x - 7y - z = -19 \\ 4x + 4y + 4z = 4 \\ 2x + y + 6z = 7 \end{array}\right. \][/tex]
### Step-by-Step Solution:
1. Write the system in matrix form:
The system of equations can be represented in the form [tex]\(AX = B\)[/tex], where [tex]\(A\)[/tex] is the coefficient matrix, [tex]\(X\)[/tex] is the column vector of variables, and [tex]\(B\)[/tex] is the column vector of constants.
[tex]\[ A = \begin{pmatrix} -1 & -7 & -1 \\ 4 & 4 & 4 \\ 2 & 1 & 6 \end{pmatrix} , \quad X = \begin{pmatrix} x \\ y \\ z \end{pmatrix} , \quad B = \begin{pmatrix} -19 \\ 4 \\ 7 \end{pmatrix} \][/tex]
2. Find the inverse of the coefficient matrix [tex]\(A\)[/tex] (if it exists):
For our purposes, it's sufficient to know that the matrix [tex]\(A\)[/tex] is invertible, and we will use the inverse to find [tex]\(X\)[/tex].
3. Multiply both sides of the equation [tex]\(AX = B\)[/tex] by the inverse of [tex]\(A\)[/tex]:
[tex]\[ A^{-1}AX = A^{-1}B \][/tex]
Since [tex]\(A^{-1}A\)[/tex] is the identity matrix [tex]\(I\)[/tex], this simplifies to:
[tex]\[ IX = A^{-1}B \quad \text{or simply} \quad X = A^{-1}B \][/tex]
4. Calculate [tex]\(X\)[/tex]:
Using the result obtained from computation:
[tex]\[ X = \begin{pmatrix} x \\ y \\ z \end{pmatrix} = \begin{pmatrix} -4 \\ 3 \\ 2 \end{pmatrix} \][/tex]
### Verification:
To ensure the solution is correct, it's good practice to substitute [tex]\(x = -4\)[/tex], [tex]\(y = 3\)[/tex], and [tex]\(z = 2\)[/tex] back into the original equations:
1. For [tex]\( -x - 7y - z = -19 \)[/tex]:
[tex]\[ -(-4) - 7(3) - 1(2) = 4 - 21 - 2 = -19 \][/tex]
2. For [tex]\( 4x + 4y + 4z = 4 \)[/tex]:
[tex]\[ 4(-4) + 4(3) + 4(2) = -16 + 12 + 8 = 4 \][/tex]
3. For [tex]\( 2x + y + 6z = 7 \)[/tex]:
[tex]\[ 2(-4) + 3 + 6(2) = -8 + 3 + 12 = 7 \][/tex]
The solution satisfies all the original equations, confirming that our solution is correct.
Thus, the solution to the system is:
[tex]\[ x = -4, \quad y = 3, \quad z = 2 \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.